IMPLEMENTING NEW METHODS OF LEARNING ENGLISH LANGUAGE AMONG NON - PHILOLOGICAL STUDENTS - Abdullayeva, D. (SCIENCE and SOCIETY, 2023)
The educational system in Uzbekistan has gone through enormous growth and development over the course of the last two decades, which has led to a number of systemic shifts as well as the introduction of some innovative new developments. As a direct result of the book's enormous significance, reading non-native works, particularly those written in the English language, has been integrated into the curricula of secondary schools all over the country beginning with the first grade.
Keywords: computer science fields and international languages; pedagogical technology; non-philological educational institutions; comprehensive system